Penerapan Media Power Point Untuk Meningkatkan Hasil Belajar PAI Pada Siswa Kelas IV SDN 12 Muara Tais Timur Kec. Mapat Tunggul Kab. Pasaman - Yustika, Yustika (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aimed to improve students' learning outcomes in Islamic Education subjects through the use of PowerPoint media. Classroom action research was conducted on fourth-grade students at SDN 12 Muara Tais Timur. The results showed an increase in students' learning outcomes after the implementation of PowerPoint media. However, there are still some obstacles that need to be overcome. This study concludes that the use of PowerPoint media can be an effective alternative to improve the quality of Islamic Education learning.